Distribusi dalam Sistem Ekonomi Islam - Ashshiddiq, Hasbi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Distribution is an important part of creating prosperity for all of its people. Islam demands that its people prioritize morality in carrying out the economy. The goal is to produce conditions of stability in the nation's economy because distribution can influence a nation's economy. The method used in this research uses the library research method, namely research by collecting data and scientific papers related to the object of research discussion or collecting data with a library nature. The distribution process in Islam. An Islamic-based economic system requires that distribution must be based on two aspects, namely freedom and justice of ownership. In Islamic economics, distribution has goals, among others, missionary goals, educational goals, social goals, economic goals, distribution also has ethics, namely, always decorating charity with the intention of worship and sincerity, transparency, fairness, mutual help, tolerance and alms, not displaying goods that giving rise to the perception, Never neglecting worship because of distribution activities, Prohibition of Ikhtikar, Seeking reasonable profits, Widespread distribution of wealth, social equality. The main aim of distribution in an Islamic perspective is to improve the welfare of society by implementing the regulations that apply in Islam.